The Effect of Self-Efficacy, Competence and Training on Employee Performance PT. Petro Oxo Nusantara Gresik - Indira Takhta Marsyada Viardhillah; Hesty Prima Rini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employee performance is a measure used to assess individual achievement because it includes various indicators to measure the quality and amount of work completed, as well as the behavior and actions of employees in carrying out their duties. Evaluation of human resource performance has an important role because it can affect the company's quality in the future. This study aims to understand the influence of Self-Efficacy, Competence, and Training on Employee Performance at PT. Petro Oxo Nusantara Gresik. This study uses a quantitative approach by taking samples from the production employees of PT. Petro Oxo Nusantara Gresik. The sampling technique used is a Saturated Sample involving 50 respondents. The data analysis method used is PLS (Partial Least Square), by conducting validity, reliability, and hypothesis testing. The findings from this study indicate that Self-Efficacy, Competence, and Training have a positive and significant impact on Employee Performance at PT. Petro Oxo Nusantara Gresik. This confirms that these factors influence employee performance in the company environment.